(untitled) (Bioscience Journal, 2015)
The aim of this study was to evaluate different alternative products, foliar sprayed either alone or in combination with fungicide fluazinam, to control white mold in soybean at three locations: Arapoti, Mauá-da-Serra, and Pinhão, in Paraná state, southern Brazil. The following chemical products were used: sodium dichloroisocyanurate, benzalkonium chloride, pyroligneous extract, sodium hypochlorite, cobalt + molybdenum, sucrose, sodium bicarbonate and acibenzolar-S-methyl. Incidence, severity, yield, and number of sclerotia produced were analyzed. The majority of the variables did not follow the normal distribution of the data according to the Kolmogorov-Smirnov test; therefore, the use of non-parametric analysis was necessary. The analysis of all the treatments individually revealed no significant effects so it was decided to separate the analysis into the following groups of treatments: ’control’, treatments using alternative products (’alternatives’), treatment only with fungicide (’fungicide’) and treatments with alternative products and fungicide (’alternatives + fungicide’). In Arapoti, no significant differences for any variables were observed. In Mauá-da-Serra, the ’fungicide’ and ’alternatives + fungicide’ had the lowest incidence and number of sclerotia, with higher yield when compared to ’control’ and ’alternatives’. No differences were observed for severity. In Pinhão, the ’fungicide’ and ’alternatives + fungicide’ were superior for incidence, number of sclerotia produced, and yield when compared to the ’control’ and ’alternatives’. The ’alternatives + fungicide’ showed significantly lower severity when compared to the control, ’alternatives’ and ’fungicide’ in Pinhão experiment. In conclusion, the alternative products applied in combination with fluazinam resulted in lower severity of white mold in soybean in the experiment conducted in Pinhão, and the application of fluazinam alone or in combination with alternative products, was efficient to control white mold in soybean in locations with high disease incidence.